2011
DOI: 10.4028/www.scientific.net/msf.679-680.269
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of Stacking Faults in PVT 4H-SiC Created by Deflection of Threading Dislocations with Burgers Vector c+a

Abstract: Synchrotron White Beam X-ray Topography studies are presented of dislocation behavior and interactions in a new generation of seventy-six millimeter diameter, 4H-SiC wafers grown using Physical Vapor Transport under specially designed low stress conditions. Such low stress growth conditions have enabled reductions of dislocation density by two or three orders of magnitude compared to the lowest previously reported levels [1]. In this paper, detailed topography analysis will be presented of the deflection of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Sato et al showed that macrosteps with heights of 100-1800 nm also led to the transformation of TSDs into Frank type stacking faults during the PVT growth of SiC [11] . The formation of stacking faults by the deflection of dislocations in the PVT growth was also shown by Dudley et al in [12]. It is conceivable that the macrosteps formed on the growth interface of crystal B led to the transformation of several threading dislocations into defects in the basal plane, leaving the crystal at the crystal flanks.…”
Section: Discussionmentioning
confidence: 55%
“…Sato et al showed that macrosteps with heights of 100-1800 nm also led to the transformation of TSDs into Frank type stacking faults during the PVT growth of SiC [11] . The formation of stacking faults by the deflection of dislocations in the PVT growth was also shown by Dudley et al in [12]. It is conceivable that the macrosteps formed on the growth interface of crystal B led to the transformation of several threading dislocations into defects in the basal plane, leaving the crystal at the crystal flanks.…”
Section: Discussionmentioning
confidence: 55%
“…The original PVT growth is carried out on the C-face of the seed crystal. As has been described previously, threading dislocations with c-component of Burgers vectors are prone to being deflected onto the basal plane close to the outer edges of the growing boules due to overgrowth by macrosteps which are prevalent in these regions due to the curvature of the growth interface [5][6]. This is shown most clearly on transmission topographs recorded from axial slices cut parallel to the growth direction of the boule as shown in Figs.…”
Section: Resultsmentioning
confidence: 85%
“…Stacking faults in the substrates have gained some attention recently and in our previous work four kinds of stacking faults have been reported in terms of their fault vectors, e.g. Shockley faults, Frank faults, Shockley plus c/2 Frank faults, and Shockley plus c/4 Frank faults [1][2][3]. Generally speaking, defects reaching the growth surface will extend into the epi layer and may potentially harm the performance of devices grown on it.…”
Section: Introductionmentioning
confidence: 98%
“…
In our previous studies [1][2][3], four kinds of stacking faults in 4H-SiC bulk crystal have been distinguished based on their contrast behavior differences in synchrotron white beam x-ray topography images. These faults are Shockley faults, Frank faults, Shockley plus c/2 Frank faults, and Shockley plus c/4 Frank faults.
…”
mentioning
confidence: 99%